Suitability of Injana Clays for filling Materials - Mohammad Rashid Abood (Tikrit Journal of Pure Science, 2023)
The study aims to evaluate suitability of injana formation clays for filling material in Sharqad area / North of Iraq, The exposed rocks are Fat’ha & Injana Formations in addition to Quaternary deposits. Three stations are studied in southern west limb of Khanuqa anticline near the north western plunge of this anticline, Geotechnical properties show that the type of soil are low plasticity (CL)and low plasticity silt(ML).The specific gravity values ranges between (2.65-2.72), the chemical analysis show that the ratio of total dissolved salts ranges between (3.9-5.2)% ,while the ratio of gypsum content ranges(2.7-3.0)%, pH values ranges between (7.8-8.0).In last the most geotechnical properties of Injana clays are accepted as filling materials for earth fill dams when compare with Iraq specification (Sorb/rs) except the ratio of (TDS) for stations,1&3.